Assessment of Foot Shape in Adult Females of Bangalee and Chakma Ethnic Groups (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background :Foot morphology differs among ethnic groups. Proper knowledge ofpopulation specific variations are necessary for industrial design and forensicinvestigations. The study was aimed to measure the foot and determine the footshape of adult Bangalee and Chakma females to find out and compare any ethnicvariation.Materials and methods: The study was conducted on 200 Chakma and 200Bangalee adult females. Foot length and foot breadth were measured by slidecaliper. Foot index was calculated and foot shape was determined from foot index.Results: Mean value for length, breadth and index of foot were significantly higherin Chakmas than Bangalees. Percentage of slender foot was higher in Bangalees andbroad foot shape was found more in Chakmas. Most of the participants of these twogroups have standard foot shape.Conclusion: Bangalee and Chakma adult females showed differences in structuralcharacteristics of foot which may be attributed to their ethnicity and environment.Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 59-62